Effect of H2O2 Antiseptic on Dispersal of Cavitation-Induced Microdroplets. (October 2021) - Roy, T.; Damoulakis, G.; Komperda, J.; Mashayek, F.; Cooper, L.F.; Rowan, S.A.; Megaridis, C.M.
The persisting outbreak of SARS-CoV-2 has posed an enormous threat to global health. The sustained human-to-human transmission of SARS-CoV-2 via respiratory droplets makes the medical procedures around the perioral area vulnerable to the spread of the disease. Such procedures include the ultrasonic dental cleaning method, which occurs within the oral cavity and involves cavitation-induced sprays, thus increasing the risk of pathogen transmission via advection. To understand the associated health and safety risks for patients and clinicians, it is critical to understand the flow pattern of the spray cloud around the operating region, the size and velocity distribution of the emitted droplets, and the extent of fluid dispersion until ultimate deposit on surfaces or escape through air vents. In this work, the droplet size and velocity distributions of the spray emerging from the tip of a free-standing common ultrasonic dental cleaning device were characterized via high-speed imaging. Deionized water and 1.5% and 3% aqueous hydrogen peroxide (H2 O2 ) solutions were used as working fluids, with the H2 O2 —an established oxidizing agent—intended to curb the survival of virus released in aerosols generated from dental procedures. The measurements reveal that the presence of H2 O2 in the working fluid increases the mean droplet size and ejection velocity. Detailed computational fluid dynamic simulations with multiphase flow models reveal benefits of adding small amounts of H2 O2 in the feed stream of the ultrasonic cleaner; this practice causes larger droplets with shorter residence times inside the clinic before settling down or escaping through air vents. The results suggest optimal benefits (in terms of fluid spread) of adding 1.5% H2 O2 in the feed stream during dental procedures involving ultrasonic tools. The present findings are not specific to the COVID-19 pandemic but should also apply to future outbreaks caused by airborne droplet transmission.